Guatemalan Refugees in Mexico: International Legal Standards - Olguin, Fernando M. (Tufts Archival Research Center, 2005)
Volume 13, Issue 2. Summer It is estimated that some 200,000 Guatemalan refugees are living in Mexico. These refugees constitute only part of a swelling worldwide refugee population, many of whom are without legal protection. In Mexico the problem has become particularly acute. Fernando M. Olguin examines how the Mexican government is dealing with its Guatemalan refugees with respect to basic customary law and international legal standards. The United Nations High Commissioner for Refugees is the recognized authority in refugee law and plays a major role in providing the day-to-day assistance in refugee camps, which Mr. Olguin describes in detail. The doctrines of asylum, non-refoulement, and temporary refuge are also discussed, and the article concludes by considering voluntary repatriation as a viable option.